Pengembangan Sistem Pemetaan Lokasi Tempat Wisata Taman Mini Indonesia Indah Berbasis Mobile - Eka Nurhuda, Septian; Purwandari, Nuraini (Institut Teknologi dan Bisnis Kalbis, 2020)
Taman Mini Indonesia Indah is one of the tourist attraction in DKI Jakarta.There was aproblems caused by the wide area of TMII. It’s confusing the visitors to know the route to the facilitywhich addressed. At each intersection around the TMII area there is a road sign, but the informationdisplayed is not concise and overlapping. The purpose of this research is to develop TMII locationmapping system. The development method used is Rapid Application Development (RAD). The resultsof this study in the form of android applications that can help TMII visitors in knowing the direction togo to the location of TMII.